Volatility, Open Interest, and Trading Volume in Indian Futures Markets - Joshi, Nisarg A. (Indian Journal of Finance, 2021)
Purpose : The paper’s objective was to scrutinize the impact of trading volume and open interest on the volatility of selected futures contracts of Indian markets. The change in notional behavior and size of such behavior was examined, and the contribution of trading volume and open interest in the behavior of the futures contract prices were investigated. Methodology and Approach : This study included a sample of daily prices for the period from 2011 – 2019 for 33 futures contracts from Indian futures markets, which included stock and commodity indices, commodities, government securities, and currencies. This study involved a two-stage methodology. In the first part, the E-GARCH model was used to investigate the disproportionate volatility response to various types of shocks. The second part of the methodology focused on investigating the coexistent relations between open interest, trading volume, and volatility using multiple regression analysis. Findings : The results showed that trading volume and open interest affected volatility, but the direction and quantum of impact depended on various variables. It was also found that trading volume and volatility had positive coexistent relations for most futures contracts. Practical Implications : These findings have substantial inferences and repercussions for portfolio managers, analysts, and investors for investment assessments and decisions regarding asset allocations in futures markets. Higher volatility will lead to a higher level of fretfulness among market participants and investors, which will push them to be more risk-averse. The results of the study also have pertinent effects for policymakers with respect to the Indian stock market and global countries. Originality/Value : The author believes that these results would magnify the volatility relations among different futures contracts.